The Remote Body: The Phenomenology of Telepresence and Re-Embodiment - Dolezal, Luna (Human Technology, 2009)
Exploring the phenomenology of remote practices made possible by recent technological advances, such as telesurgery, will reveal the role of proprioception in agency and ownership of action and furthermore delimit the possibility of re-embodiment through technological interfaces. An understanding of the lived body, viewed through the philosophical paradigms of theorists Husserl and Merleau-Ponty, will demonstrate the role of the corporeal schema and intercorporeality in an agent’s interaction with the immediate environment and hence elucidate the limits of achieving a seamless remote interaction as good as the "real thing." These considerations are fundamental for grounding the bioethical, legal, and epistemological issues that arise in remote interaction, particularly in the case of telesurgery.